Preventive Effect of Ultraviolet Photofunctionalization on Peri-implant Biofilm Formation: An In vivo Randomized Study - Akanksha Goel; Vinit Swami; Amol Somaji Patil; Vasanthi Vinit Swami (Wolters Kluwer Medknow Publications, 2024)
Background: Peri-implant biofilm formation due to local bacterial colonization is one of the important factors for the instability of temporary anchorage devices (TADs). Aim: The aim of this study was to quantify and compare the colonization of Streptococcus sanguinis on ultraviolet (UV) treated and untreated titanium TADs. Materials and Methods: This prospective, in vivo study included 20 subjects requiring orthodontic treatment with first premolar extraction, followed by retraction of the anterior teeth with absolute anchorage using TADs. TADs were placed interdentally, in the keratinized tissue between the upper second premolar and the first molar on the buccal side, at the mucogingival junction. It was a split-mouth study where one side of TAD was UV-treated for 15 min, and the other side was kept untreated as a control. TADs were removed after 6 months for S. sanguinis quantification on both sides and were compared for biofilm reduction. Statistical Analysis: Statistical software was used to perform unpaired t-tests for the individual samples as well as for comparing total UV-treated and untreated samples. P <0.05 was considered significant. Results: The mean bacterial count (per ml) was found to be 2.2 × 106 copy numbers and 8.9 × 106 copy numbers in the UV group and untreated group, respectively. The total count of bacteria was found to be less in the UV-treated group compared to the untreated group. Conclusions: The study concludes that UV photofunctionalization results in a significant reduction of S. sanguinis colony on TADs with reduced chances of failure due to inflammation.